2005
DOI: 10.1080/01419870420000315843
|View full text |Cite
|
Sign up to set email alerts
|

A politics of resentment: Shopkeepers in a London neighbourhood

Abstract: In this article we analyse the "talk" of shopkeepers in a multicultural London neighbourhood. These shopkeepers resent the loss of economic prosperity and sense of community that, in their nostalgic recollection, characterized their neighbourhood in an earlier era. They answer the classic question of politics, "who gets what and why" with "they get everything because we get nothing." We identify this stance as a politics of resentment, one that engages with government and media narratives against asylum-seeker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 2 publications
0
21
0
Order By: Relevance
“…The ideological blend of radical-right parties [i.e., combining a centrist economic program with welfare chauvinism and protectionism (Mudde, 2000)] may be especially attractive to those in vulnerable forms of self-employment. Self-employed individuals in economically and socially precarious conditions, may exhibit a ''politics of resentment'' by seeking to punish mainstream politics for their relative misfortunes (Wells and Watson, 2005;Standing, 2011). Hence, hypotheses 3 assumes that people in precarious selfemployment are outsiders in the political system.…”
Section: Diverging Political Alignmentsmentioning
confidence: 99%
“…The ideological blend of radical-right parties [i.e., combining a centrist economic program with welfare chauvinism and protectionism (Mudde, 2000)] may be especially attractive to those in vulnerable forms of self-employment. Self-employed individuals in economically and socially precarious conditions, may exhibit a ''politics of resentment'' by seeking to punish mainstream politics for their relative misfortunes (Wells and Watson, 2005;Standing, 2011). Hence, hypotheses 3 assumes that people in precarious selfemployment are outsiders in the political system.…”
Section: Diverging Political Alignmentsmentioning
confidence: 99%
“…Brown (2000), Greenfeld (1992) and others have argued that the early modern nationalisms derived from the unfulfilled social ambitions of new elites articulated as being 'for the people', enabling suppressed class aims to be expressed as national ideology. More recently, nationalist ideology and racist neo-nationalisms have been interpreted as grounded in the anger and social resentments of petit-bourgeois (Wells and Watson 2005) and working-class populations who see their livelihoods and once-protected social institutions being threatened. The combination of class frustrations, changed social environments and anti-immigrant sentiments is the social foundation of neo-nationalist and populist politics in most European states (Svallfors 2004;Taylor-Gooby 2004).…”
Section: Discussion: Class Indifference and Resentmentmentioning
confidence: 99%
“…For example, many studies have found differences in national sentiment to be strongly linked to social class (Dowds and Young 1996), with nationalist and racist sentiments the most prominent amongst the working class and petite bourgeoisie (Wells and Watson 2005), and with the highly educated middle classes reporting weaker national sentiments. Equally, however, such approaches are limited by a 'one-dimensional' approach which treats the nation as one of a range of social identities that neither overlap nor interact (Phillips 2002: 598Á9).…”
Section: Introductionmentioning
confidence: 97%
“…Soysal, 1994;Luchtenberg, 1998;Licata & Klein, 2002;Gijsberts, 2004;De Vreese & Boomgaarden, 2005;Wells & Watson, 2005;Van Peer, 2006). In Germany, immigrants from Turkey make up the most important immigrant population.…”
Section: Notions Of the European Union In Terms Of Inclusivenessmentioning
confidence: 98%